2018
DOI: 10.1080/00221686.2018.1473296
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic resistance in open-channel flows over self-affine rough beds

Abstract: Knowledge of hydraulic resistance of single-valued self-affine fractal surfaces remains very limited. To advance this area, a set of experiments have been conducted in two separate open-channel flumes to investigate the effects of the spectral structure of bed roughness on the drag at the bed. Three self-affine fractal roughness patterns, based on a simple but realistic three-range spectral model, have been investigated with spectral scaling exponents of − 1, − 5/3 and − 3, respectively. The different widths o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 33 publications
0
64
0
Order By: Relevance
“…The relative offsets between the velocity profiles when plotted versus z/H reflects the expected trend of increasing friction factor (∼u 2 * /U 2 ) with decreasing relative submergence (H/D; e.g. Stewart et al 2018). Analysis in Cameron et al (2017) indicated that for these flows the measured velocity distributions support a logarithmic range up to z/H ≈ 0.5 with a von Kármán coefficient of κ = 0.38.…”
Section: Resultsmentioning
confidence: 62%
“…The relative offsets between the velocity profiles when plotted versus z/H reflects the expected trend of increasing friction factor (∼u 2 * /U 2 ) with decreasing relative submergence (H/D; e.g. Stewart et al 2018). Analysis in Cameron et al (2017) indicated that for these flows the measured velocity distributions support a logarithmic range up to z/H ≈ 0.5 with a von Kármán coefficient of κ = 0.38.…”
Section: Resultsmentioning
confidence: 62%
“…This effect was observed to be as great as 49 % between the R1 and R3 beds and it was not dependent on the channel aspect ratio. The present paper is, to a certain degree, a follow up of the work reported in Stewart et al (2019), with a particular focus on the mechanisms contributing to the overall friction factor. 3.2.…”
Section: Roughness Characteristicsmentioning
confidence: 96%
“…Its equivalent presentation k s ≈ (0.88-1.13)∆ provides additional support for choosing ∆ = 4σ z for characterising roughness heights in our study. Besides, Stewart et al (2019) also showed that the spectral slope β appears to be closely related to the roughness 'effective slope' ES, which is equal to the double solidity λ (i.e. the ratio of the projected frontal area of the roughness elements to the wall-parallel projected area; Napoli, Armenio & De Marchis 2008;Flack & Schultz 2010).…”
Section: Roughness Characteristicsmentioning
confidence: 98%
See 2 more Smart Citations